Perilaku Praktek Soft Budget Constraint dalam Penganggaran di Pemerintah Daerah (Studi Kasus Pemerintah Provinsi Maluku Utara) - Gestalt Ekya Nalendra; Abdul Hadi Sirat; E. Hartaty Hadady (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
The main problem of this research is that in the management of regional finances in Indonesia, especially the North Maluku Provincial Government, there is a vertical fiscal imbalance, low commitment, and high information asymmetry that triggers practices. The purpose of this study is to explore information that occurs in the regional financial management of North Maluku Province to find out and identify the Behavioral Practices of soft budget constraints on regional financial management of North Maluku Province. The research method used in this study is a qualitative descriptive research method with a case study approach. This research focuses intensively on one particular object under study as a case. The results of this study indicate that the local government to solve financial problems is very weak. This can be seen from the APBD-P compiled by the North Maluku Provincial Government, which has a deficit and instead tends to increase SIKPA. Even though under these conditions, the provincial government should have implemented a surplus budget so that it could cover the previous year's SIKPA.